Evolution of diagnostic criteria for arrhythmogenic right ventricular cardiomyopathy and their application in clinical practice - Yu. A. Lutokhina; O. B. Blagova; A. G. Shestak; E. V. Zaklyazminskaya; S. A. Alexandrova; A. V. Nedostup (Российский кардиологический журнал)
This article describes evolution of criteria for arrhythmogenic right ventricular dysplasia/cardiomyopathy (ARVD/C). The novel diagnostic criteria for ARVD/C published in 2020 are analyzed in detail, among which biventricular and leftdominant arrhythmogenic cardiomyopathy are identified for the first time. The need to develop novel criteria was fed on the accumulation of new data on ARVD/C, in particular, significant advances in magnetic resonance imaging technologies. The novel criteria retained high sensitivity and specificity in relation to traditional right ventricular disease form and became more sensitive in relation to the biventricular and left-dominant arrhythmogenic cardiomyopathy.Nevertheless, the addition of left-dominant disease forms reduces the criteria specificity in general, since left ventricle involvement with a similar clinical performance can have different etiology that goes beyond the ARVD/C, even when mutations are detected in typical genes, which is demonstrated by case reports described in the article. Like the previous two versions, the novel criteria will be fully assessed only with a large sample of patients after their introduction into the routine cardiology clinical practice.